2022
DOI: 10.3389/fendo.2022.830347
|View full text |Cite
|
Sign up to set email alerts
|

High Remnant Cholesterol Level Potentiates the Development of Hypertension

Abstract: BackgroundEmerging evidence suggests an association between remnant cholesterol (RC) and vascular damage and hypertension. However, this association has not been explored in a large-scale population in China, and a temporal relationship between RC and hypertension also needs to be investigated.MethodsWe conducted a retrospective cross-sectional study in 2,199,366 individuals and a longitudinal study in 24,252 individuals with repeated measurements of lipid profile and blood pressure in at least a 3-year follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Additionally, a study of a population of 7308 individuals recruited from CHNS showed that the concentration of RC was associated with DM beyond the LDL-C [30]. Besides, RC also had a substantial connection with the prediction or diagnosis of hypertension, and could be used as a blood marker for screening [31,32]. All of the above evidence indicated that RC level was highly relevant to cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, a study of a population of 7308 individuals recruited from CHNS showed that the concentration of RC was associated with DM beyond the LDL-C [30]. Besides, RC also had a substantial connection with the prediction or diagnosis of hypertension, and could be used as a blood marker for screening [31,32]. All of the above evidence indicated that RC level was highly relevant to cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Adverse cardiovascular events related to RC have also been observed in many clinical studies. High levels of RC have been reported to be associated with an increased risk of coronary artery disease, fatty liver disease, hypertension, and chronic kidney disease 11,12,[33][34][35] . FMD, which is a marker of endothelium-dependent dilation of the brachial artery, reflects systemic endothelial function, as well as atherosclerotic risk burden at the time of FMD measurement.…”
Section: Discussionmentioning
confidence: 99%
“…We could speculate that there is a potential biological interaction. SIDT2 is an integral membrane protein associated with cholesterol uptake from the extracellular space into the cell via endocytosis [ 59 ]. The binding to cholesterol by the SIDT2 protein is performed specifically by the transmembrane Cholesterol Recognition/interaction Amino acid Consensus (CRAC) domain.…”
Section: Discussionmentioning
confidence: 99%